Kontribusi resiliensi terhadap motivasi belajar siswa broken home - Renanda Nurul Meydiana; Tanti Ardianti; Burhanudin Burhanudin (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
the purpose of this research is to find out whether there is a positive and significant relationship between resilience and the learning motivation of broken home students. The school that became the subject of this research was SMP Negeri 12 Depok. The type of research used in this study is quantitative research, using a descriptive approach and interview, questionnaire and observation methods. The results of this study indicate that there is a significant influence between resilience and learning motivation of broken home students at SMP Negeri 12 Depok. This is shown based on the results of hypothesis testing which shows a significant value (2-tailed) instrument 0.000 < 0.05, then H0 is rejected and H1 is accepted, so it can be concluded that there is a significant relationship between resilience and learning motivation of broken home students at SMP Negeri 12 Depok.